Thermal performance of 3D-printed buildings - Sovetova, Meruyert (2025)
3D printing in construction offers a sustainable alternative to conventional methods, with advantages such as geometric flexibility, reduced waste, cost and time savings. However, the high costs associated with large-scale 3D printers constrain the widespread adoption of additive manufacturing in construction. This research addresses this limitation by designing, calibrating, and evaluating an affordable lab-scale 3D printer tailored for cement-based materials, aiming to lower the entry barriers for additive manufacturing research in construction.